Analyzing Errors Voiced Stop for Buginesss Language Community at SMK Negeri 1 Pangkajene Sidrap - Ahmad Risal Majid; Rasmi Rasmi (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to analyze the pronunciation errors of the voiced stop /d/ among students in the English language community at SMK Negeri 1 Pangkajene Sidrap. The research focuses on identifying the extent of students’ ability to correctly pronounce words containing the voiced stop /d/, a common challenge in English phonology for non-native speakers. The respondents consisted of 15 students selected from various classes. Data were collected through pronunciation tests including minimal pairs, sentences, and a paragraph containing multiple instances of /d/. Students' voices were recorded and analyzed to identify errors and calculate individual scores. The results revealed that the majority of students had significant difficulty distinguishing voiced stop /d/ from its voiceless counterpart /t/, often mispronouncing words such as bad as bat. The average score was 31, which indicates a very poor level of mastery. The findings suggest that most students lack awareness of the phonological rules related to voiced stops, are unfamiliar with certain vocabulary, and are influenced by their native language patterns. The study recommends that English teachers provide more targeted instruction, repetitive drills, and practical speaking activities focused on voicing distinctions to improve students’ pronunciation accuracy.